MEDIA SMART BOARD SEBAGAI UPAYA MENINGKATKAN HASIL BELAJAR PKN SISWA KELAS 2 PADA MATERI IMPLEMENTASI SILA PANCASILA - Safirra Wahyu Citera Purnama; Dwi Krisna Maulida; Susilo Tri Widodo; Nur Indah Wahyuni; Theresia Tri Rubiyanti (STKIP Subang, 2023)
This research aims to develop Civics learning outcomes through the Pancasila smart board media for class IIA students at SDN Kalibanteng Kidul 01. This exploration uses a descriptive qualitative research strategy carried out in two cycles. The subjects of this examination were 29 class IIA students at SDN Kalibanteng Kidul 01. Research data was obtained through observation, tests and field notes. Observation data on learning exercises are analyzed in the form of percentages and average scores in learning. Test data on student learning outcomes is broken down by entering scores to be surveyed and considering the level of learning fulfillment. Field data containing various obstacles is broken down and then arrangements are sought. The results of the research show that the use of the Pancasila smart board media can further develop the Civics learning outcomes of class II students at SD Negeri Kalibanteng Kidul 01. This can be seen from the increase in the normal scores of students who obtained results of 74% in the first cycle year to 86% in the second cycle. Apart from that, traditional climax results also increased from 74% in cycle I to 93% in cycle II. The increase in learning outcomes is caused by several variables, including: the use of attractive and intuitive Pancasila smart board media can increase students' attraction and inspiration in learning and can better help students understand. Keywords: Pancasila Smart Board Media, Learning Outcomes, PPKn